Privacy breach perceptions and litigation intentions: Evidence from e-commerce customers. Issue 4 (December 2021) - G, Rejikumar; V, Gopikumar; Dinesh, K.G.Sofi; Asokan-Ajitha, Aswathy; Jose, Ajay
Abstract: This paper examines the formation of litigation intentions among e-commerce customers under the privacy breach due to the influence of antecedents such as vulnerability, social risk, privacy dispositions, effectiveness privacy policy, awareness of data management and moderators such as privacy control beliefs, efficacy in coping and litigation complexity. A structural equation modelling analysis revealed that reasons for privacy breach perceptions are customer dispositions about privacy, anticipated vulnerability due to privacy breach, and social risk related to personal information disclosure. The control beliefs and coping skills of customers under privacy threat positively moderate litigation intentions. Similarly, the task complexity of litigation significantly reduces litigation intentions.